Development of a low-cost culture medium from industrial and environmental by-products for sustainable cultivation of Lactic Acid Bacteria - Michele Letitia Tchabou Tientcheu; Pierre Marie Kaktcham; Edith Marius Foko Kouam; Laverdure Tchamani Piame; Lysette Chabrone Djodjeu Kamega; Agnihotri Shekhar; Singh Bhim Pratap; François Zambou Ngoufack (PLoS ONE, 2025)
Conventional culture media such as de Man, Rogosa and Sharpe are essential for the growth of lactic acid bacteria and the production of metabolites used in the food and pharmaceutical industries. However, their high cost limits their application, particularly in low and middle-income countries. This study aimed to develop a cost-effective and efficient culture medium based on agro-industrial and environmental by-products, pineapple peels, sugarcane molasses, and black soldier fly larvae cake. After physico-chemical analysis of the by-products, excluding sugarcane molasses, a statistical mixture design was used to determine the optimal proportions for supporting lactic acid bacteria growth and bacteriocin production. Growth and metabolite production were monitored via plate count and agar well diffusion assays respectively. The strains tested belonged to the genera Lactobacillus , Bifidobacterium , Streptococcus , Lactococcus, and Bacillus as an out taxa group. The larvae cake showed high protein (48.47 ± 0.14%) and amino acid (17 types) content, while pineapple peels and molasses were rich in carbohydrates (89.52 ± 0.16% and 86.86 ± 0.07%). Based on regression models, the compromise formulation was defined as 55.15% larvae cake hydrolysate, 19.85% pineapple peel hydrolysate, and 25.00% sugarcane molasses. This medium highly supported lactic acid bacteria growth (9.43–9.86 log CFU/mL) compared to MRS and M17 (9.20–9.69 log CFU/mL), with Lactobacillus strains performing better. It also supported bacteriocin activity (11.0–14.5 mm inhibition zones), higher or similar to MRS and M17, with Lactococcus lactis subsp. lactis MA2 exhibiting the strongest effect. These results highlight the potential of this formulation as a sustainable, low-cost alternative for microbiology and biotechnology, particularly in resource-limited settings. The determination of its formula will allow its manufacture once the proximate compositions of the ingredients are known, regardless their origin. Future investigations will focus on optimisation of culture conditions, powder form formulation, and cost evaluation.